Performance Analysis of Smart Antenna Based on MVDR Beamformer using Rectangular Antenna Array - Suhail Najm, Shahab; Ayib Rosdi, Zainun; Nurul Hazlina, Noordin; Ahmad Johari, Mohamad; Omar, Khaldoon A. (Asian Research Publishing Network (ARPN), 2015)
The performance of smart antenna system greatly relies on the beam forming technique that forming the main lobe beam pattern to the desired user direction and place null in the direction of undesired interference source. This paper investigates the implementation of Minimum Variance Distortionl ess Response (MVDR) Adaptive Beam-Forming (ABF) algorithm on Rectangular Antenna Array (RAA) is discussed and analyzed. The MVDR ABF technique performance is studied in accordance with varying the number of array elements, spacing between the array element s, the number of interference sources, noise power label, and the number of snapshots. The MVDR performance is compared on the basis of output radiation pattern and SINR. Computer simulation results show that the performance of the MVDR improved as the number of elements get more. This mean MVDR strongly depends on the number of the element. 0.5λ is considered the best spacing between adjacent antenna elements, the performance degraded as the noise power label increased, and more accurately resolution occurred when the number of snapshots increased